SEJARAH LOKAL KAMPUNG KACUNG DI BANGKA BARAT (1900–1949): DARI PERMUKIMAN NOMADEN KE DESA PASCA-KEMERDEKAAN - Mahendra Mahendra; Farida R. Wargadalem; Helen Susanti (Universitas Batanghari Jambi, 2026)
This study is aimed at reconstructing the history of Kampung Kacung in West Bangka within the framework of colonialism as a relation of power and the formation of contemporary social identity construction. Until now, the origins of the village have mostly existed in the form of folklore and the collective memory of the local community without systematic academic documentation. The research uses a qualitative approach with methods of heritage oral history and critical literature review. Data was obtained through in-depth interviews with local community leaders, descendants of the village founders, as well as elderly residents, and was then analyzed thematically and interpretatively with the triangulation of recent literature. Research results show that the formation of Kampung Kacung began from the pre-settlement phase, marked by labor mobility within the tin mining economic orbit, and then integrated into the administrative structure of the colonial regime through the afdeling system and the East–West Ketapik division. The construction of road infrastructure after Depati Amir's resistance strengthened the colonial regime's oversight, while the tax structure tied the local community into an economic system that produced social stratification. In this context, the term